"Flow-void" sign in osseous metastatic renal cell carcinoma. Issue 2 (February 2019) - Murphy, J.; Patel, A.; James, S.L.; Botchu, R.; Davies, A.M.
Abstract : Aim: To evaluate the frequency of the "flow-void" sign in a large series of pathologically proven renal cell carcinoma (RCC) bone metastases referred to a specialist unit and to evaluate its correlation with both lesion size and imaging sequence. A further aim was to describe a proposed grading system for the description of the "flow-void" sign. Materials and methods: A retrospective review of patients with magnetic resonance imaging (MRI) of pathologically proven RCC bone metastases between September 2007 and December 2017 was performed. MRI images were reviewed for the presence of the "flow-void" sign and a proposed grading system for this sign was applied. Statistical analysis was performed to determine the association between the presence of the "flow-void" sign and lesion size and MRI sequence. Results: One hundred and forty bone lesions in 123 patients with histologically proven metastatic RCC were reviewed. One hundred and thirty-two (94.3%) lesions demonstrated the "flow-void" sign on at least one sequence in each study. A statistically significant difference was demonstrated between lesion size and the presence and type of "flow-void" sign. Lesions demonstrating type 3 "flow-void" sign had mean dimensions of 82.2 mm compared to 47.3 mm for lesions that did not demonstrate the "flow-void" sign ( χ 2 (2) =11.4; p =0.01). T2-weighted, proton density and fat-saturated imaging also demonstrated the "flow-void" sign more frequently. Conclusion: The "flow-void" sign is a common imaging feature within RCC bone metastases. When observed, the "flow-void" sign can be a useful imaging feature in the diagnosis of RCC bone metastases. Highlights: Renal cell carcinoma bone metastases can present as solitary bone lesions. "Flow void" sign is frequently seen in renal cell carcinoma bone metastases. "Flow void" sign becomes more conspicuous with increasing lesion size.